Moving to a better place? Residential mobility among families with young children in the Millennium Cohort Study - Ludovica Gambaro; Heather E. Joshi; Ruth Lupton (Population, Space and Place, 2017)
This paper assesses how far residential moves can result in improvement or deterioration of the housing and neighbourhood circumstances for families with young children. It uses data from the UK Millennium Cohort Study concentrating on the time between infancy and age 5, 2001 to 2006. First, we ask which families moved home and in what circumstances. We then examine how moving changed several aspects of housing: space standards, damp problems, and tenure. We show that the majority of moves resulted in improvements to housing conditions, especially in reducing overcrowding. We also consider neighbourhood circumstances, proxied by a measure of local poverty at small-area level. Movers generally ended up in neighbourhoods with lower levels of poverty, or no worse, but almost one fifth of moves were downward or remained in the 30 percent poorest areas. We ask whether locating in an area with more local poverty may help achieve a larger home. There is evidence of such a trade-off—1 in 5 families moved to a larger home, which was either in a poorer area than before or remained in the 30 percent poorest areas. We conclude by showing how the path of upward housing mobility, while numerically dominant, was far less common among families with relatively low resources and whose moves were attendant on partnership changes. For them, moves often result in smaller homes in poorer areas.
Keywords: 330; Cohort Studies; Early childhood; Housing quality; Neighbourhood poverty; Residential mobility